2012
DOI: 10.1111/azo.12018
|View full text |Cite
|
Sign up to set email alerts
|

A morphological, morphometric and histochemical study of the oviduct in pregnant and non‐pregnant females of the plains viscacha (Lagostomus maximus)

Abstract: Flamini, M.A., Barbeito, C.G. and Portiansky, E.L. 2014. A morphological, morphometric and histochemical study of the oviduct in pregnant and nonpregnant females of the plains viscacha (Lagostomus maximus). -Acta Zoologica (Stockholm) 95: 186-195.The oviduct is a very thin organ with a very tortuous appearance. It is divided into three segments: the infundibulum, the ampulla and the isthmus. Particularly, the oviduct of the viscacha lacks the intramural portion described in other species. The mucosa shows long… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 31 publications
2
7
0
1
Order By: Relevance
“…It is impossible to compare our results with others as the cycle effect on the oviductal infundibulum in other primates has not been investigated. The absence of fucose residues has also been observed in the oviductal infundibulum of porcine [ 49 ] and plains viscacha ( Lagostomus maximus ) [ 50 ]. Distinct OGP has been detected in the infundibulum of several mammals [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is impossible to compare our results with others as the cycle effect on the oviductal infundibulum in other primates has not been investigated. The absence of fucose residues has also been observed in the oviductal infundibulum of porcine [ 49 ] and plains viscacha ( Lagostomus maximus ) [ 50 ]. Distinct OGP has been detected in the infundibulum of several mammals [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…El mismo mostró características similares a las descriptas para otros mamíferos, pudiendo diferenciarse sus regiones anatómicas (infundíbulo, ampolla, istmo y porción intramural). La presencia de numerosas flexuras lo asemejó al de los roedores múridos, rumiantes, équidos y suidos (Beck et al), así como a histricomorfos como la vizcacha de llanura (Lagostomus maximus) (Flamini et al, 2014), el puercoespín de cola de pincel (Atherurus africanus) (Mayor et al, 2003), el puercoespín crestado (Hystrix cristata) (Ozdemir, 2004) y la paca (Cuniculus paca) (Goncalves dos Reis et al, 2011).…”
Section: Discussionunclassified
“…The uterine tube is a part of female reproductive system which receives the Oocyte and provide a good situation for fertilization. The results showed that the uterine tube was tortuous, whitish to fleshy color and flexible organ with narrow lumen [7]. The uterine tube tortuousness is related to pre and reproductive life [8].…”
Section: A Morphological Measurementsmentioning
confidence: 99%